Cloacal reconstruction after a complex treatment of perineal haemangioma in a variant of PELVIS syndrome. Issue 1 (December 2015) - Zalimas, Algirdas; Posiunas, Gintas; Strupas, Sigitas; Raugalas, Ramunas; Raistenskis, Juozas; Verkauskas, Gilvydas
Abstract Background PELVIS is an acronym defining the association of perineal hemangioma, malformations of external genitalia, lipomyelomeningocele, vesicorenal abnormalities, imperforate anus and skin tag. Eleven cases have been reported according to the Orphanet data. Acronyms of LUMBAR and SACRAL syndrome have been used and most probably represent a spectrum of the same entity. Very little is known about the success and timing of cloacal reconstruction after the treatment of hemangioma. We present a variant of PELVIS syndrome and discuss the possibilities and optimal timing of surgical reconstruction. Case presentation Female infant was born with persistent cloaca and multiple hemangiomas of genitals, perineal area and left thigh. Colostomy was performed after birth. In order to treat hemangioma and to make the reconstruction of cloaca possible, corticosteroid treatment orally and multiple laser treatments were performed alternating Nd:YAG laser and pulsed dye laser therapy. Cystoscopy confirmed hemangiomatosis in the mucosa of the common channel, bladder neck and septate vagina. Oral propranolol treatment was started at the age of 18 months and continued for 1 year. It induced rapid improvement of hemangiomas. Two more pulsed dye laser treatments were performed to remove residuals of hemangiomas from the perineum and genital area. Posterior sagital reconstruction by separation of the rectum, mobilization of urogenital sinus and vaginal reconstruction was performed with no major bleeding at the age of 4 years. Postoperatively, after a period of progressive rectal dilatation colostomy was closed. Girl is now 6 years old, dry day and night without residual urine and normal upper tracts. Rectal calibration is normal, fecal continence is still to be evaluated but constipation is easily manageable. CT of the spine and the perineum showed sacral dysplasia and spina bifida with lumbo-sacral lipoma and tethering of terminal filum without neurological deterioration at the moment but requiring close neurological monitoring. Conclusions Large perineal hemangiomas are commonly associated with extracutaneous abnormalities. Successful reconstructive surgery is possible after significant reduction of hemangioma by complex treatment.